Do clean fuel and trade-openness reduce environmental degradation in China: evidence from asymmetric model - Shakeel, Muhammad; Nobre, Catarina (Frontiers in Energy Research, 2024)
This research investigates the effects of output, clean fuel, and trade on environmental pollution, aiming to assess the decomposed effect of clean fuels resources and trade in mitigating pollution and promoting environmental sustainability. By employing Nonlinear auto-regressive distributed lags (NARDL) approach on time series data from 1990-2020, the study discovers that economic growth and development contributes to increase pollution levels, while the utilization of clean fuels exhibits a modest yet significant curbing impact and vice versa. However, the smaller coefficient values underscore the need for an increased share of clean fuels in energy mix and the implementation of additional measures to control pollution. Furthermore, the analysis reveals a noteworthy negative relationship between trade and pollution emissions, although pollution emissions corroborate a declining trend over time. These findings support the potential of clean fuel adoption and trade promotion in China. Nevertheless, they also emphasize the importance of regulatory policies, public awareness campaigns, and investments in sustainable technologies to attain long-term environmental sustainability of the country.